The Relationship of Self-Regulation and Resilience in Parents of Attention Deficit Hyperactivity Disorder (ADHD) at Special School-C Karya Tulus Tuntungan II - Riko Hengki Nababan; Jenny Marlindawani Purba; Wardiyah Daulay (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Attention deficit hyperactivity disorder is a mental development disorder that becomes a problem for parents if it is not treated immediately. So that parents can increase their resilience and bounce back from difficulties wisely. The type of research is descriptive quantitative with a cross-sectional approach. This research aims to analyze the relationship between self-regulation and the resilience of parents with children with ADHD at Special School-C Karya Tulus Tuntungan II. The type of research is descriptive quantitative with a cross-sectional approach. Technique. Sampling is purposive sampling. This research's respondents were parents with children with ADHD at Special School-C Karya Tulus Tuntungan II, totalling 50 respondents. This research was carried out from March 27 to May 5 2024. The instruments used were the Connor-Davidson Resilience Scale (CD-RISC) and the self-regulation questionnaire (SRQ). Data were analyzed using the Spearman rank statistical test. The results of the study showed that the majority of respondents (74.0% had self-regulation in the capable category, there was a strong positive relationship between self-regulation and the resilience of parents who have children with ADHD with a Pearson correlation value of +0.450, p-value -value=0.001; p>0.05). The conclusion is that there is a relationship between self-regulation and the resilience of parents who have children with ADHD at Special School -C Karya Tulus Tuntungan II, which is quite strong and in the same direction. It is recommended as a nursing intervention that can be developed to explore self-regulation and resilience in patients and families, especially in parents who have children with ADHD.Keywords: ADHD, parent, Self-regulation, Resilience